2018
DOI: 10.1113/jp273425
|View full text |Cite
|
Sign up to set email alerts
|

Phase waves and trigger waves: emergent properties of oscillating and excitable networks in the gut

Abstract: The gut is enmeshed by a number of cellular networks, but there is only a limited understanding of how these networks generate the complex patterns of activity that drive gut contractile functions. Here we review two fundamental types of cell behaviour, excitable and oscillating, and the patterns that networks of such cells generate, trigger waves and phase waves, respectively. We use both the language of biophysics and the theory of nonlinear dynamics to define these behaviours and understand how they generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Human and animal studies have shown that, in contrast to the stomach and small intestine, the colon pacemaker activity is labile and does not show a persistent frequency gradient . If the frequency is “noisy,” that is, if it fluctuates around, for example, 12 cpm, both at the proximal and distal end of the cyclic motor pattern activity, propagation direction will be “chaotic” and can switch direction quickly and can occur simultaneous; in a system of coupled oscillators, the propagation is not determined by sequential depolarization of consecutive cells but rather by the synchronization of cyclic electrical activities with or without phase lags . The high‐frequency cyclic motor pattern consists of rather randomly alternating retrograde and antegrade propagating, or simultaneous pressure waves.…”
Section: Discussionmentioning
confidence: 99%
“…Human and animal studies have shown that, in contrast to the stomach and small intestine, the colon pacemaker activity is labile and does not show a persistent frequency gradient . If the frequency is “noisy,” that is, if it fluctuates around, for example, 12 cpm, both at the proximal and distal end of the cyclic motor pattern activity, propagation direction will be “chaotic” and can switch direction quickly and can occur simultaneous; in a system of coupled oscillators, the propagation is not determined by sequential depolarization of consecutive cells but rather by the synchronization of cyclic electrical activities with or without phase lags . The high‐frequency cyclic motor pattern consists of rather randomly alternating retrograde and antegrade propagating, or simultaneous pressure waves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dislocations are seen (within the oval), a sudden termination of a propagating contraction. These ripple properties illustrate that the ripples are orchestrated by a system of coupled oscillators, the interstitial cells of Cajal 54,55 (A)…”
Section: Noradrenaline Effects On Ripple Frequencymentioning
confidence: 99%
“…Undoubtedly many motility patterns emerge from the interaction between excitable and oscillatory cells in the super network, depending on physiological conditions (20). We have barely begun to examine these excitatory-oscillatory interactions and modulations but understanding them and the behaviour they produce in the super-network will be achieved by careful synchrony between experiment and mathematical models (20,(28)(29)(30)(31).…”
Section: The Gastrointestinal Musculature As a Super Networkmentioning
confidence: 99%